Pengaruh Putaran Mill Jar Pada Proses Penghalusan Serbuk Keramik Alumina dengan Alat Horizontal Ball Mill - Ade Indra (Kelompok Peneliti Muda Universitas Negeri Jakarta, 2023)
Powder technology is one of the most frequently used alumina manufacturing processes. The powder must be made as small as possible because the mechanical strength of the ceramic is inversely proportional to the size of the powder. Powder grinding can be done using a horizontal ball mill. Ball mill is equipment that functions to grind powdered material with the help of grinding balls inside it. The purpose of this study was to determine the effect of variations in the rotational speed of the mill jar on the quality of alumina powder products at room temperature. The research method used is the experimental method by testing the alumina powder material with variations in the rotation speed of the mill jar 100 rpm, 125 rpm, 150 rpm, 175 rpm, 200 rpm, 225 rpm and 250 rpm. The results of the study showed that variations in the rotational speed of the mill jar affected the size of the alumina powder which was ground using a ball mill. The best mill jar rotation speed from this test was 150 rpm, resulting in a sub-micron size percentage of 8.0% and a reduction in the size of alumina powder from 70.28 µm to 44.07 µm.